ENTREPRENEURIAL INNOVATION IN TRADITIONAL WEAVING CRAFTSMEN DESIGNED BATIK FOR IMPROVING THE TOURISM INDUSTRY IN KLATEN - Sri Murni; Rahmawati Rahmawati; Siti Nurlaela; Celviana Winidyaningrum (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2011)
The target of this study is to improve skilled knowledge and attitude worker of weave fasten as that self-supporting as according to potency and also opportunity work at industrial company, which is on finally can improve the quality of its life. Special target of this study give the knowledge of entrepreneurship among worker of weave fasten so that have high job ethos and also can yield pre-eminent masterpieces capable to compete in global market. The implementation take place to start 16 July until 23 July 2010, what consist of three phase that is activity early stage cover preparation phase, middle phase of activity which phase execution of training and also final phase of activity covering phase handling of post training. This training assign value added because there is skilled of batik design innovation at weave fastens affecting at make-up of production addition. The next study shall earn to measure effectiveness of “transfer training” on so that will be able to know how far done training can alter behavior of educative participant plunging in corporate world and industrial world and also trying self-supporting.